Excel For Accounting Untuk Penyusunan Laporan Keuangan Pada Yayasan Panti Asuhan - Eka Rosalina; Wiwik Andriani; Afridian Wirahadi; Fera Sriyuniati; Desi Handayani (Akuntansi dan Manajemen, 2020)
Financial Statements is an accounting process that are arranged and reported objectively which can be useful for its users. Each financial statement preparation must be based on applicable financial accounting standards. One of them is the preparation of financial statements for the foundation. A foundation is a legal entity that has the aims and objectives of social, religious and humanitarian benefits. Case Study conducted at the Shine Al-Falah Foundation. The procedures in preparing the financial statements of the Al Falah foundation start from with studying the transactions in the form of cash in and cash out transaction books. After that, a needs analysis is made in the preparation of financial statements using Exel For Accounting which starts from plan the Account List, making ledgers, work sheet and continuing to design the Financial Statements of the Foundation. Last is to provide assistance and training to the preparation of financial statements using Exel for Accounting.